Acyl‐CoA synthetase 6 regulates long‐chain polyunsaturated fatty acid composition of membrane phospholipids in spermatids and supports normal spermatogenic processes in mice. Issue 12 (25th October 2019) - Shishikura, Kyosuke; Kuroha, Sayoko; Matsueda, Shinnosuke; Iseki, Hachiro; Matsui, Takeshi; Inoue, Azusa; Arita, Makoto
Abstract : Long‐chain polyunsaturated fatty acids (LCPUFAs), such as docosahexaenoic acid (DHA, 22:6) and docosapentaenoic acid (DPA, 22:5), have versatile physiologic functions. Studies have suggested that DHA and DPA are beneficial for maintaining sperm quality. However, their mechanisms of action are still unclear because of the poor understanding of DHA/DPA metabolism in the testis. DHA and DPA are mainly stored as LCPUFA‐containing phospholipids and support normal spermatogenesis. Long‐chain acyl‐conenzyme A (CoA) synthetase (ACSL) 6 is an enzyme that preferentially converts LCPUFA into LCPUFA‐CoA. Here, we report that ACSL6 knockout (KO) mice display severe male infertility due to attenuated sperm numbers and function. ACSL6 is highly expressed in differentiating spermatids, and ACSL6 KO mice have reduced LCPUFA‐containing phospholipids in their spermatids. Delayed sperm release and apoptosis of differentiated spermatids were observed in these mice. The results of this study indicate that ACSL6 contributes to the local accumulation of DHA‐ and DPA‐containing phospholipids in spermatids to support normal spermatogenesis.—Shishikura, K., Kuroha, S., Matsueda, S., Iseki, H., Matsui, T., Inoue, A., Arita, M. Acyl‐CoA synthetase 6 regulates long‐chain polyunsaturated fatty acid composition of membrane phospholipids in spermatids and supports normal spermatogenic processes in mice. FASEB J. 33, 14194‐14203 (2019). www.fasebj.org